Proposal to Improve Warehousing Activities and Warehouse Arrangement of Clothing Stores Using The Lean Warehousing Method - H. A. Tanisri, Roberta; Ibnuh, Muhammad; Nugroho Aji, Sonny; Yunan Pribadi, Agustinus; Hedi Saepudin, Tubagus (Dinasti Information and Technology, 2023)
Maysara Clothing Store Warehouse is a storage place for fashion products of various types and colors. There are several problems in the process of shipping goods where there are often product inconsistencies that reach consumers. This caused complaints from consumers. This research aims to provide suggestions for improvements in terms of the process of warehousing activities and warehouse arrangement owned by the Maysara Clothing Store. The problem-solving approach method used is lean warehousing. The lean warehousing method is a method that can be used to find out what types of activities have the potential to cause waste. The most common type of waste that occurs in the Maysara Store warehouse is waste. Improvement proposals that can be applied to reduce this type of waste are in the form of implementing 5S in all warehouse areas, making standard work instructions in every warehousing activity, and arranging the warehouse by adding lighting points in the warehouse area and the work area of Toko Maysara warehouse employees.